Model Pembelajaran Quantum Teaching Untuk Meningkatkan Hasil Belajar Siswa MI/SD Kelas II B Tema 6 Subtema 3 - Nur Hakim (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
This study aims to improve the theoretical learning outcomes theme 6 subtema 3 (Plants around me) through the use of quantum teaching models in grade II students MI Darul Ulum Sendangharjo. This type of research is collaborative type classroom action research. The research was conducted in class II B MI Darul Ulum Sendangharjo which is located at Jl. Main Poros no. 88 Sendangharjo Brondong Lamongan. The subjects of this study are students of class II B, amounting to 27 students and the object of research is the improvement of thematic learning result theme 6 subtema 3 (Plants around me). Data collection is done by using tests, observations, and documentation. The instruments used are multiple choice questions and observation sheets. Data analysis technique used qualitative and quantitative descriptive data analysis. The results showed that the quantum teaching model can improve the thematic learning outcomes of the theme 6 subtema 3 (Plants around me) grade II students MI Darul Ulum Sendangharjo with TANDUR step; step growth by giving song, natural step by giving direct experience, naming step with giving task, step demonstration by presenting, step repeat with question and answer, and step celebrate with giving praise. The increase is shown through the results of the test, the average cycle I reached 69.11 and increased in cycle II to 76.30, and the increase again in cycle III, which reached 84, 15.